Sinus Valsalva Dissection with Involvement Right Ostium Artery during PCI Rescue: A Rare Complication - Scianna Salvatore (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Aorto-coronary dissection is a rare complication that occur during percutaneous coronary intervention, but life threatening. We describe a case of limited iatrogenic dissection of Valsalvae, with ostium right coronary artery, during a PCI rescue perfomed via trans-radial approach and was successfully treated without surgical intervention.